Rdo rje rnal ʼbyor maʼi sgo nas gśin po rjes su ʼdzin paʼi cho ga thar lam ʼdren paʼi lcags kyu źes bya ba bźugs so - Rmor-chen Kun-dgaʼ-lhun-grub, 1654-1726 (Sa-ṅor Chos-tshogs, 1968)
Funeral ritual of the Sakyapa sect of Tibetan Buddhism utilizing the propitiation of Vajrayoginī